2003
DOI: 10.1007/s00428-003-0842-y
|View full text |Cite
|
Sign up to set email alerts
|

Chymase-positive mast cells in small sized adenocarcinoma of the lung

Abstract: Mast cells accumulate in angiogenesis-dependent situations of lung adenocarcinoma. Human mast cells are divided into two major subsets: MCT (mast cells with immunoreactivity for tryptase but not chymase) and MCTC (reactive for tryptase and chymase). Chymase is an important mediator of tissue remodeling, but research into chymase-containing mast cell subpopulations has been hampered by the lack of reagents suitable for use with formalin-fixed tissue. We stained chymase using CC1 antibody in 66 cases of small si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…Furthermore, MCs are important for the structural maintenance of skin through the production of growth factors and fibroblasts (Erbagci and Erkiliç 2002;Maurer et al 2003). It is important to state that the participation of mast cells in epithelial remodeling and tissue repair after actinic damage has also been reported (Grimbaldeston et al 2006;Humphreys et al 2000;Huttunen and Harvina 2005;Nagata et al 2003;Wang et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, MCs are important for the structural maintenance of skin through the production of growth factors and fibroblasts (Erbagci and Erkiliç 2002;Maurer et al 2003). It is important to state that the participation of mast cells in epithelial remodeling and tissue repair after actinic damage has also been reported (Grimbaldeston et al 2006;Humphreys et al 2000;Huttunen and Harvina 2005;Nagata et al 2003;Wang et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…28 Of note, in the present study, the bronchioloalveolar cell carcinoma group had extremely low endothelial-cell VEGFR-3 expression among histologic subtypes of lung adenocarcinomas. Because bronchioloalveolar cell carcinoma has very low stromal induction, such as a few mast cell densities 30 and low fibroblast proliferation, 36 induction of tumor lymphangiogenesis in this subtype is thought to be very low. VEGFR-3 expression was also observed in tumor cells in NSCLCs.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells were counted in the serial sections at sites where they had accumulated most intensively. 30 Macrophages, excluding alveolar macrophages, were counted in the serial sections at the sites where they had intensively accumulated in the stroma of the tumor. For mast cell evaluation, perivascular, peribronchial, and peribronchiolar regions within tumors were excluded.…”
Section: Immunohistochemical Staining Methodsmentioning
confidence: 99%
“…Some studies have shown that mast cell infiltration correlates with angiogenesis and poorer prognosis in early-stage lung adenocarcinoma (42,43), whereas others have shown that the prognosis of lung adenocarcinoma is not influenced by the extent of mast cell infiltration (44,45). Although the results of these studies are quite different with respect to the prognostic roles of mast cells, both previous studies and the current study consistently showed that mast cell infiltration is more intensive in well-differentiated tumors and low-grade histologic subtypes than in poorly differentiated and high-grade subtypes (44,45). The findings on the prognostic values of mast cells in this study may, therefore, be attributed to the different measuring method used for mast cells; previous studies counted mast cells in regions with the highest mast cell densities (42-44), whereas we used the number of mast cells in the predominant histologic subtype (to enable valid comparisons with other types of infiltrating immune cells).…”
Section: Discussionmentioning
confidence: 99%